Optimising polyacrylamide (PAM) spray application to mitigate the agronomic effects of Soil Crust. - Arpano, Silvia (Cranfield University, 2022)
The Leafy greens industry provides micronutrient-rich fresh produce at an affordable price. To meet the demand, multiple short crop cycles per year are seeded and harvested, for example, the summer spinach cycle can be as short as 21 days with 4 to 6 crop cycles in a season, in the UK. However, this high input/output agronomic system has a negative impact on other provisioning and regulating ecosystem services (ES). The primary soil-related ES that are affected are sequestration of soil carbon, crop production and water storage. The intensive soil management strategy promotes on-field loss of soil organic matter, which reduces soil resilience to erosive forces and contributes to the formation of capping and sealing. Soil capping and sealing inhibits seedling emergence, which reduces crop productivity. Within the rapid management cycle of leafy greens production there is limited time to incorporate soil amendments to offset the loss of SOM. This research explores the use of polyacrylamides (PAMs) as a soil surface amendment within this cropping system. Polyacrylamides are molecules with a long carbon backbone characterised by areas of different electric charge density. This trait allows them to bind to polar substance (e.g. water, soil colloids, soils organic matter). They are excellent flocculants and have been used for decades in furrow-irrigated crops to mitigate soil erosion and increase water infiltration. Besides flocculating particles in free-flowing water, PAMs have also been found to bind and protect soil aggregates by being adsorbed into aggregates and stabilising them. In combination, these two properties of PAMs have the potential to mitigate the agronomic effects of soil capping and sealing, including reducing emergence impedance, reducing splash contamination, and promoting water infiltration. However, PAMs are very hygroscopic and can be difficult to work with at concentrations above 500 ppm in water. This research investigated a new PAM broadcast system, using a Dual-Fluid nozzle which mixes PAM and water outside of the hydraulic system. The effect of PAMs on soil and crops were measured in a laboratory experiment and in five field trials on two crops, coriander and spinach. The metrics measured included soil crust, soil moisture, emergence and final yield quantity and quality. The results of the research have shown the efficacy of PAM within commercial leafy greens crops. The application of PAM was associated with earlier emergence in coriander, that lead to higher biomass per plant and it also increased the emergence count in spinach, leading to an overall higher yield (47- 39% for plots treated with 80 kg ha⁻¹ of PAM and 80kg ha⁻¹ PAM+Ca respectively). The amount of soil splash, and therefore potential for contamination of the product, was also reduced (24, 41 and 59% decrease in splash detached soil from plots treated with 40, 80 and 120 kg ha⁻¹ PAM respectively compared to the control). An economic appraisal based on the field data, also determined that PAM could be economically viable within the commercial cropping system and identified future improvements.
Deeks, Lynda K. - Associate Supervisor
Keywords: dual-fluid nozzle; synthetic soil conditioners; water use efficiency; splash erosion; infiltration; emergence homogeneity